PITCH PROFILE OF THE GLOTTAL WHISTLE (M4) - Edgerton, Michael Edward; Tan, Samuel; Evans, Gabriel; Myung, Hwa Jang; Bo, Kyung Kim; Loo, Fung-Ying; Pan, Kok-Chang; Hashim, Mohd Nasir (Malaysian Journal of Science, 2013)
This paper presents a previously unreported method of laryngeal vocal sound production that is capable of producing pitches even higher than the whistle register (M3). Colloquially known as the glottal whistle (here referred to as M4), this method has a wider range than M3 and features frequent instances of biphonation, which is of interest for those involved with contemporary and improvised music. Pitch profile analyses of M4 have found the majority of fundamental frequency (f0) activity to be between 1 and 3 kHz, while the most frequently seen range was between 1000 to 1,500 Hz. Remarkably, multiple singers were able to produce f0 higher than the highest tone on the piano. (Keywords: glottal whistle, whistle register, M3, voice science, high fundamental frequency)